2002
DOI: 10.1193/1.1516753
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Retrofitting of R/C Shaft Support of Elevated Tanks

Abstract: The circular, reinforced concrete (R/C) shaft-type support for elevated tanks lacks redundancy, damping and additional strength typically present in building framing systems and, therefore, should be designed for larger seismic resistance. However, the Indian seismic code IS:1893-1984 prescribes the same basic seismic force as that for the most ductile building framing system for which the design force is the least. Furthermore, the code-specified one-mass idealization of elevated water tanks is not appropriat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 8 publications
0
28
0
Order By: Relevance
“…Rai [3] studied the performance of elevated tanks in the 1997 Jabalpur and Bhuj earthquake of 2001. It was concluded that with low axial load, small longitudinal steel ratio, and a thick wall, acceptable ductility is gained for RC pedestals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rai [3] studied the performance of elevated tanks in the 1997 Jabalpur and Bhuj earthquake of 2001. It was concluded that with low axial load, small longitudinal steel ratio, and a thick wall, acceptable ductility is gained for RC pedestals.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated water tanks have not performed up to expectations in many earthquakes in the past. The poor performance of these structures in the past earthquakes such as Chile 1960 [1] (due to design deficiency), Manjil-Roudbar 1990 (out of date design standards) [2], Jabalpur 1997 and Gujarat 2001 [3] has been reported in the literature. Extent of damages has been ranging from minor cracks in the pedestal up to complete collapse of the entire structure.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, elevated tanks should remain functional in the post-earthquake period to ensure water supply is available in earthquake-affected regions. Nevertheless, several elevated tanks were damaged or collapsed during past earthquakes (Haroun and Ellaithy, 1985;Rai, 2002). Therefore, the seismic behavior of elevated tanks should be known and understood, and they should be designed to be earthquake-resistant.…”
Section: Introductionmentioning
confidence: 98%
“…Rai [9,20,21] has studied RC shaft-elevated water tanks affected by strong events, proposing techniques for their rehabilitation and recommending alterations on world codes to significantly reduce the ductility of these types of structures. These recommendations follow the same design philosophy of EC-8 [18], ACI [16], IBC [17] and IITK-GSDMA [19], among other codes.…”
Section: Damage Observed In Past Earthquakesmentioning
confidence: 99%